COVID-19 disparity among racial and ethnic minorities in the US: A cross sectional analysis. Issue 38 (November 2020) - Tirupathi, Raghavendra; Muradova, Valeriia; Shekhar, Raj; Salim, Sohail Abdul; Al-Tawfiq, Jaffar A.; Palabindala, Venkataraman
Abstract: Aim: To analyze racial disparities in Coronavirus disease (COVID-19) cases in the United States of America and discuss possible reasons behind this inequality. Subject and methods: We obtained estimated case counts of African-American, Caucasian, Native American, Asian and Hispanic individuals with coronavirus disease (COVID-19)infection through May 5, 2020, from publicly available data on state departments of health websites. We calculated race-specific fractions as the percentage of the total population and analyzed the reasons behind this disparity. Results: The incident rates of COVID-19 were higher among African Americans and among Latinos disproportionately higher than their representation in 14 states and 9 states, respectively. A similar observation was also reported for New York city. The percentage of deaths reported among African Americans was disproportionately higher than their represented share in the population in 23 out of 35 states. It was reported that 22.4% of COVID-19 deaths in the USA were African American, even though black people make up 13.4% of the USA population. Conclusions: The analysis shows the disparity of coronavirus disease outcomes by ethnicity and race. Additional research is needed to determine the factors behind this inequality.